Condensation of Hydrocarbons in Compact Smooth and Microfinned Tubes - Ehsan Allymehr; Ángel Álvarez Pardiñas; Trygve Magne Eikevik; Armin Hafner (Energies, 2021)
A database for flowing condensation of three hydrocarbons, namely propane (R290), isobutane (R600a), and propylene (R1270), is extended by experimental tests in a smooth tube and two microfinned tubes with an increase of heat exchange area of 1.51 and 2.63, respectively. The outer diameter for all of the test tubes was 5 <semantics>mm</semantics>. Heat transfer coefficient and pressure drop are compared between the fluids and tubes. Tests were conducted at saturation temperatures of 35 °C and mass fluxes between 200 to 500 <semantics>kgm−2s−1</semantics>. Results show that isobutane (R600a) has a higher heat transfer coefficient and pressure drop while propylene (R1270) and propane (R290) present very similar characteristics. Both microfinned tubes increase the heat transfer coefficient compared to the smooth tube, but with different magnitude and tendencies and almost independently of the fluid tested. The maximum increase of heat transfer coefficient reached values of up to 1.8 while the maximum increase in pressure drop was by a factor of 1.7. Data have been compared with predictive methods exhibiting accurate correlation for smooth tube, while the accuracy of results for the microfinned are dependent on the type of tube and fluid used.